THE USE OF YOUTUBE AS MEDIA TO IMPROVE SPEAKING SKILL STUDENT'S IN THE ELEVENTH GRADER OF SMAN 3 SAMPANG - Arikah Bahiroh (The Ellite of Unira, 2024)
Speaking is a skill of comprehending the meaning to pronounce something fluently and accurately. In EFL learning, many students must know pronunciation grammar, vocabulary, fluency, comprehension. the teacher do many ways and many learning methods to improve their students' speaking skills. this study aims to describe the strategy of using YouTube to improve speaking skill and to describe the result of using YouTube to improve speaking skill. This study uses a qualitative descriptive method with field notes observation and interview documentation to obtain data. The informants used purposive sampling with the category of students being the most able to speak in class, resulting seven English students at the SMAN 3 Sampang as the sample. The results of this study could conclude students were very enthusiastic and pleased in using Youtube as a media to improve talks and strategies for the use of YouTube media to improve students’ speaking skills to fit with YouTube media.